Clinical Evaluation of Nasopharyngeal, Oropharyngeal, Nasal Swabs, and Saliva for the Detection of SARS-CoV-2 by Direct RT-PCR - Sergei A. Kiryanov; Tatiana A. Levina; Vladislava V. Kadochnikova; Maria V. Konopleva; Anatoly P. Suslov; Dmitry Yu. Trofimov (Diagnostics, 2022)
Nasopharyngeal swab (NPS) and oropharyngeal swab (OPS) are the most widely used upper respiratory tract specimens for diagnosis of SARS-CoV-2 using RT-qPCR. In contrast, nasal swab (NS) and saliva (SS), recently recommended by the WHO, are rarely used, and their test accuracy is limited. The method for direct RT-PCR detection of SARS-CoV-2 does not require an RNA extraction and is faster and easier than standard RT-PCR tests with RNA extraction. This study aimed to compare the diagnostic performance of upper respiratory tract samples for SARS-CoV-2 detection using the direct RT-PCR without preliminary heat inactivation. Here we report the application and validation of direct RT-PCR SARS-CoV-2 RNA on 165 clinical specimens of NPS/OP, and 36 samples of NS/NPS and 37 saliva samples (for the latter with prior deproteinization). The overall sensitivity estimates were 95.9%, 94.2%, 88.9%, and 94.6% for NPS/OPS/NS/SS samples, respectively, and the specificity was 100% against standard RT-PCR with RNA extraction. Overall, NS and SS testing by direct RT-PCR had sufficient sensitivity to detect SARS-CoV-2. They can be acceptable alternative to NPS/OPS for rapid detection of SARS-CoV-2 infections in future.